2020
DOI: 10.1101/2020.11.24.396002
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Initial ciliary assembly inChlamydomonasrequires Arp2/3 complex-dependent endocytosis

Abstract: Cilia are organelles important for signaling and motility. They are composed of microtubules ensheathed in plasma membrane. The mechanisms related to ciliogenesis also require another cytoskeletal element, actin, which has been shown to be important for organizing the basal bodies and transition zone at the base of cilia and for short- and long-range trafficking. However, most studies of actin’s role in ciliogenesis have taken a broad approach by knocking out all filamentous actin until now. Here, we more deli… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 86 publications
0
8
0
Order By: Relevance
“…Membrane trafficking in Chlamydomonas has been found to be important for maintaining ciliary length and for ciliary assembly. Previous studies have shown that the Golgi-derived membrane is important for ciliary assembly and maintenance (Dentler, 2013), and inhibiting internalization through Arp2/3 complex perturbation also results in defective ciliary assembly and maintenance (Bigge et al, 2023). Although EM of the Golgi trial (n = 30, N = 3).…”
Section: Bci Disrupts Membrane Traffickingmentioning
confidence: 97%
“…Membrane trafficking in Chlamydomonas has been found to be important for maintaining ciliary length and for ciliary assembly. Previous studies have shown that the Golgi-derived membrane is important for ciliary assembly and maintenance (Dentler, 2013), and inhibiting internalization through Arp2/3 complex perturbation also results in defective ciliary assembly and maintenance (Bigge et al, 2023). Although EM of the Golgi trial (n = 30, N = 3).…”
Section: Bci Disrupts Membrane Traffickingmentioning
confidence: 97%
“…Previously, Bigge et al 2020 showed that actin puncta formation, reminiscent of endocytic pits seen in yeast, were absent in ARPC4 cells. In the presence of BCI, actin puncta increased both in steady state cells ( Fig 5B-C ) and in regenerating cells ( SF 3B ).…”
Section: Resultsmentioning
confidence: 98%
“…Membrane trafficking in Chlamydomonas has been found to be important for maintaining cilia length and for ciliary assembly. Previous studies have shown that Golgi-derived membrane is important for ciliary assembly and maintenance (Dentler, 2013), and inhibiting internalization through Arp2/3 complex perturbation also results in defective ciliary assembly and maintenance (Bigge et al, 2020). While EM of the Golgi showed no noticeable differences in Golgi structure ( SF 3A ), collapsing the Golgi with BFA (Brefeldin A) intensified ciliary shortening when paired with 20 µ M BCI, suggesting that BCI alters other membrane pathways outside of Golgi derived membrane for ciliogenesis ( Fig 5A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The process of protein trafficking to the primary cilium is supported by many players involved in endocytosis and the vesicle transport machinery [24][25][26] . Prominent among them are small GTPases, which act as molecular switches that allow for the guidance of their associated vesicles [27][28][29] .…”
Section: Introductionmentioning
confidence: 99%